A comparison of extraluminal and intraluminal use of the Uniblocker in left thoracic surgery: A CONSORT-compliant article. Issue 21 (May 2017) - Liu, Zhuo; He, WenSheng; Jia, QianQian; Yang, XiaoChun; Liang, ShuJuan; Wang, XiuLi
Abstract: Background: The aim of this study was to assess the feasibility and safety issues concerning extraluminal use of the Uniblocker for one-lung ventilation (OLV) in the left thoracic surgery. Methods: Forty patients undergoing elective left thoracic surgery were included in this study, and all patients were randomly allocated to extraluminal use of Uniblocker group (E group, n = 20) or intraluminal use of Uniblocker group (I group, n = 20). Time for intubation, time for verification of the correct position of Uniblocker, incidence of Uniblocker displacement, index of pulmonary collapse, mean arterial pressure, heart rate, peak airway pressure, oxygen saturation in two-lung ventilation, and 30 minutes after OLV, bronchial damage after OLV, sore throat, and hoarseness postoperative were recorded. Results: The time for positioning Uniblocker was 112.6 ± 31.2 seconds in intraluminal use group, whereas the time for positioning Uniblocker was significantly shorter in extraluminal use group (63.4 ± 15.8 seconds). The incidence of main bronchial injury, the time of intubation, the incidence of Uniblocker malposition after initial placement, the time of OLV, the degree of pulmonary collapse, mean arterial pressure, heart rate, peak airway pressure, oxygen saturation in two-lung ventilation, and 30 minutes after OLV, the incidence of sore throat and hoarseness postoperative have no statistical significance ( P  > .05). Conclusion: Extraluminal use of the Uniblocker was proved to be a more rapid and more accurate method than conventional intraluminal use of the Uniblocker for OLV in left thoracic surgery.